Primary pancreas NTRK-rearranged neoplasm harboring an EVT6::NTRK3 fusion with a sclerosing epithelioid fibrosarcoma morphology: a case report and comprehensive review of the literature - Wu, Xin; Li, Dujuan; Fu, Fangfang; Lian, Lifei (Frontiers in Oncology, 2025)
NTRK-rearranged spindle cell neoplasms (NTRK-RSCNs) are an emerging soft tissue tumor entity characterized by NTRK gene fusions, occurring predominantly in the extremities of children and young adults. The diagnosis of this tumor is challenging due to its nonspecific and highly variable morphology. Given the response to selective NTRK inhibitors, it remains critical to identify the rare cases occurring in the viscera of adults. Here, we report a 53-year-old woman who presented with a new abdominal mass of half a month’s duration. Magnetic resonance imaging (MRI) showed a mass localized in the body and tail of the pancreas, leading to a partial pancreatectomy. Histologically, the tumor showed that bland monomorphic spindle cells were arranged in single rows of lines along the collagen fiber, reminiscent of sclerosing epithelioid fibrosarcoma. Immunohistochemically, the spindle cells focally expressed CD34 and S100 but lacked SOX10, MUC-4, Desmin, CK, and STAT6 expression. The tumor also showed cytoplasmic reactivity for pan-tyrosine receptor kinase (pan-TRK). Fluorescence in situ hybridization (FISH) analysis of NTRK1/NTRK2/NTRK3 gene break-apart probes identified NTRK3 rearrangement. Subsequent next-generation sequencing revealed EVT6 exon4::NTRK3 exon14 fusion. After surgery, the patient received continuous treatment with larotrectinib for 22 months and was followed up for 22 months without any signs of recurrence or metastasis. To further understand the clinical features, pathology, treatment and prognosis of this tumor, we searched the literature using different combinations of keywords ultimately obtaining 164 cases of NTRK-RSCNs (including the present case). Of these cases, 97 (59.1%) occurred in viscera, and 67 (40.9%) in soft tissues. There may be differences in age, histomorphology, immunophenotype, genetics, and prognosis between visceral and soft tissue NTRK-RSCNs. Appropriate immunohistochemical workup, including CD34, S100, and pan-TRK, and molecular tests, are indispensable in identifying this entity.